2019
DOI: 10.1186/s13568-019-0914-2
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of Bacillus species-derived surfactin on Brachyspira hyodysenteriae and Clostridium perfringens

Abstract: Swine dysentery and necrotic enteritis are a bane to animal husbandry worldwide. Some countries have already banned the use of antibiotics as growth promoters in animal production. Surfactin is a potential alternative to antibiotics and antibacterial agents. However, the antibacterial activity of Bacillus species-derived surfactin on Brachyspira hyodysenteriae and Clostridium perfringens are still poorly understood. In the current study, the antibacterial effects of surfactin produced from Bacillus subtilis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 30 publications
2
39
0
Order By: Relevance
“…Here, the fermented feed additive contained the live B. licheniformis and B. licheniformis-derived antimicrobial peptide surfactin. It has been reported that surfactin isolated from BLF can inhibit the growth of diarrhea-associated pathogens, such as Clostridium perfringens and Brachyspira hyodysenteriae [14,24]. Surfactin also exhibited an anti-inflammatory effect without cytotoxicity in vitro [25,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, the fermented feed additive contained the live B. licheniformis and B. licheniformis-derived antimicrobial peptide surfactin. It has been reported that surfactin isolated from BLF can inhibit the growth of diarrhea-associated pathogens, such as Clostridium perfringens and Brachyspira hyodysenteriae [14,24]. Surfactin also exhibited an anti-inflammatory effect without cytotoxicity in vitro [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…The prevention of post-weaning diarrhea by the application of probiotics or probiotic-derived functional metabolites has also been investigated in weaning piglets [9][10][11]. Among the probiotic strains that have been studied, Bacillus licheniformis has been reported to have a strong ability to produce digestive enzymes and antimicrobial peptides that enhance nutrient utilization and inhibit pathogen growth [12][13][14]. Furthermore, the combined use of B. licheniformis and Bacillus subtilis have been found to decrease the morbidity and mortality rates, ameliorate enteritis, and improve the growth performance of weaning piglets [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Prevention of C. perfringens -induced necrotic enteritis with the use of probiotics or probiotic derived metabolites has been increasingly studied ( Knap et al , 2010 ; Abudabos et al , 2013 ; Cheng et al , 2018 ; Lin et al , 2019 ). Bacillus licheniformis , a gram-positive and endospore-forming probiotic strain exhibits in vitro antibacterial activity against C. perfringens through the production of the antibacterial cyclic lipopeptide surfactin ( Thaniyavarn et al , 2003 ; Barbosa et al , 2005 ; Horng et al , 2019 ). Our previous studies have shown that surfactin isolated from B. licheniformis -fermented products can suppress the growth of C. perfringens, Brachyspira hyodysenteriae , and Staphylococcus aureus in vitro ( Horng et al , 2019 ; Lin et al , 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bacillus licheniformis , a gram-positive and endospore-forming probiotic strain exhibits in vitro antibacterial activity against C. perfringens through the production of the antibacterial cyclic lipopeptide surfactin ( Thaniyavarn et al , 2003 ; Barbosa et al , 2005 ; Horng et al , 2019 ). Our previous studies have shown that surfactin isolated from B. licheniformis -fermented products can suppress the growth of C. perfringens, Brachyspira hyodysenteriae , and Staphylococcus aureus in vitro ( Horng et al , 2019 ; Lin et al , 2019 ). Furthermore, B. licheniformis is able to mitigate C. perfringens -induced necrotic enteritis and ameliorate growth performance in broilers ( Knap et al , 2010 ; Liu et al , 2012 ; Gong et al , 2018 ; Musa et al , 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation